FONOLOGI BAHASA MUNA: KAJIAN TRANSFORMASI GENERATIF - Siti Fatinah (Multilingual, 2013)
Muna language which is still spoken and preserved by its people has arbitrary ign system of language sound. Each of the sounds are difference, particularly when it is analyzed by the aspect of diferentation.Based on the fact, the phonology of Muna language which is analyzed based on generative transformation method is analyzed on this paper. There are two problems that would be escribed; (1) how the realization of the phonology of Muna language, in phonemics or phonetics evel (2) how the realization of the characteristics of the phonem differentiation in Muna languages. The theory which is applied is degenerative phonology one by Chomsky. The data is collected by theclosed-interview, open-interview, and noted techniques. Next, the data is analyzed by the intralingual similarity method by the similarity link and differentiate link technique. The data is written by formal and informal method. In the result, it is shown that Muna language has 18 vocal segments, there are /i/, /ii/, /i:/, /u/, /u:/, /I/, /U/, /e/, /e:/, /E/, /ee/, /A/, /o/, /o:/, /O/, /a/, /a:/, and aa/. The consonants segments are 26, there are : /p/, /b/, /mp/, /mb/, /m/, /W/, /-b /, /f/, / ɸ/, /t/, /d/, /-d/, /s/, /nt/, /ns/, /nd/, /n/, /r/, /l/, /k/, /g/, / X/, /Gk/, /Gg/, /G/, and /h/. By the 14 distinguished character, it is found that all of Muna language vocal have characters as [+sil]; /mp/, /m/, /W/, /nt/, /ns/, /nd/, /n/, /r/, /l/; [+son] is the characters of all consonants excepts the semivocal which has characters as [+kon]; characters [+kont] is attached by the phonem /f/, /P/, /s/, /X/, /h/; All of the phonemes in theMuna language do not have characters [+ppt]; /f/, /P/, /s/ has character[+strid]; the character [+nas] has been attached by nasal and pre nasal phonemes; the characters is [+lat] only attached by phonem /l/; phonemes /p/, /b/, /mp/, /m/, /-b/, /f/, /P/, /t/, /d/, /-d/, /s/, /nt/, /ns/, /nd/,/n/, /r/, /l/ haveharacter [+ant]; phonem /t/, /d/, /-d/, /s/, /ns/, /nd/,/n/, /r/, /l/ have character [+kor]; the character[+tin] is attached by /W/, /k/, /g/, /X/, /Gk/, /Gg/, /G/, /i/, /ii/, /i:/, /u/, /u:/; the characters [+ren] is attached by //h/, /A/, /a/, /aa/, /a:/; phonemes /W/, /k/, /g/, /X/, /Gk/, /Gg/, /h/, /u/, /u:/, /U/, /e/, /e:/, /E/, /ee/, /A/, /a/, /aa/, /a:/; and the character [+bul] is attached with the phonemes /u/, /u:/, /U/, /o/,/o:/, /O/.